2014
DOI: 10.3386/w20491
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and Financial Development: Evidence from U.S. Counties in the 19th Century

Abstract: This paper uses data on fertility and financial development in 19th century U.S. to test the hypothesis that more developed local financial markets reduce the incentives for families to have a large offspring to provide for them at old age, the so-called old-age security hypothesis. We find that the presence of banks is associated to lower children-to-women ratios and crude birth rates even after controlling for a large set of socio-economic factors. To account for possible endogeneity of bank location we inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
(71 reference statements)
1
16
0
Order By: Relevance
“…The study finds that better access to capital markets decreases fertility. Recently, Basso et al (2014) have shown that the presence of a bank and the degree of financial development in a given county are strongly associated with lower children-towomen ratios. Using data for 78 countries over the period 1995-2010, Filoso and Papagni (2015) find that credit availability increases fertility, while access to capital market decreases fertility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study finds that better access to capital markets decreases fertility. Recently, Basso et al (2014) have shown that the presence of a bank and the degree of financial development in a given county are strongly associated with lower children-towomen ratios. Using data for 78 countries over the period 1995-2010, Filoso and Papagni (2015) find that credit availability increases fertility, while access to capital market decreases fertility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At lower quantiles such as τ = 0.10 and 0.25, the FLPR is not rejecting the null hypothesis, however, the FLFP is giving a negative relationship toward the FR after reaching quantile τ = 0.50 onward. The female labor participation is getting attention in recent studies among South Asian countries, and most of the finding show that fertility rate decline as increase of financial development and female labor force participation (Filoso & Papagni, 2015;Idris et al, 2018); Fox et al, 2018;Basso, Bodenhorn, & Cuberes, 2014;Hafner & Mayer-Foulkes, 2013). For example, Lee et al (2012) highlighted female labor's involvement and FR in women employment with a negative relationship effect.…”
Section: Max Mean Skewnessmentioning
confidence: 99%
“…The data also found that self-financing expansion of social security reduces fertility and rises household saving. Another convincing evidence on old-age hypothesis done by Basso et al (2014) found that the presence of bank and developed local financial market are strongly associated with lower children-to-women ratios. This was observed using the data from 196 counties in the Northeastern United States (Connecticut, Delaware, Massachusetts, New Hampshire, New Jersey, New York, Pennsylvania, Rhode Island, and Vermont) in the 19th century.…”
Section: Fertility and Financial Developmentmentioning
confidence: 92%